2017
DOI: 10.14198/jhse.2017.121.06
|View full text |Cite
|
Sign up to set email alerts
|

The differences in acceleration, maximal speed and agility between soccer, basketball, volleyball and handball players

Abstract: Complex reaction speed, acceleration, maximum speed, speed of whole -body change of direction and agility represent the basic components of sport performance mainly in sport games and combat sports. However, contradictory findings have been reported as to the extent of the relationship between the different speed and agility components. This study comprised 117 players (soccer -56, basketball -17, volleyball -20, and handball -24) playing youth leagues U15-U17 who were assessed for 10-m sprint (acceleration), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 4 publications
1
30
0
2
Order By: Relevance
“…As for the sport-specific physical demands of these two team sport modalities, soccer demands greater number of movements performed in the sagittal plane (i.e. sprinting) [ 9 ], whereas basketball players perform more movements in the frontal plane (i.e. shuffling), and require greater jumping demands [ 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…As for the sport-specific physical demands of these two team sport modalities, soccer demands greater number of movements performed in the sagittal plane (i.e. sprinting) [ 9 ], whereas basketball players perform more movements in the frontal plane (i.e. shuffling), and require greater jumping demands [ 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Šimonek, Horička and Hianik (2017) although negative relationship was observed between speed and agility performances in football players Little and Williams (2005) study who found a weak correlation between speed and agility in male soccer players. This result is similar to our study.…”
Section: Discussionmentioning
confidence: 92%
“…Peningkatan pengetahuan gizi pada atlet memiliki peran dalam pemilihan makanan dan minuman yang tepat, sehingga tingkat pengetahuan gizi yang tinggi dapat menunjang peningkatan ketahan fisik serta menunjang prestasi atlet. 13 Berdasarkan hasil penelitian, tingkat kelincahan (Tabel 2) responden remajalaki-laki tergolong kategori sangat baik sebesar 73,8% dan memiliki rata-rata sebesar 14 Hasil status hidrasi (Tabel 2) menunjukkan bahwa responden laki-laki sebesar 97,6% dan perempuan sebesar 100,0% yang berarti status hidrasi seluruh responden termasuk kategori tidak mengalami dehidrasi. Hal ini terjadi karena banyak ditemukan responden mengkonsumsi air ditiap 30 menit selama latihan berlangsung bertujuan untuk memenuhi cairan tubuhnya, sehingga tidak mengalami dehidrasi selama atau setelah latihan.…”
Section: Pendahuluanunclassified